219k views
0 votes
Describe the translation. y=(x+3)2+4 → y=(x+1)2+6

User Adrenalin
by
6.2k points

1 Answer

1 vote

Answer:

Shift +2 units to the right and +2 units up

Explanation:

y = (x+3)² + 4 has a horizontal shift of -3 and a vertical shift of +4.

y = (x+1)² + 6 has a horizontal shift of -1 and a vertical shift of +6.

So do translate the first equation to the second, shift +2 units to the right and +2 units up.

User Sdgfsdh
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.